THE INFLUENCE OF WORK FAMILY CONFLICT, WORK STRESS AND WORKLOAD ON THE ON THE PERFORMANCE OF NIKS KONVEKSI EMPLOYEES IN SURAKARTA - Damayanti, Elviana Monika; Ahsani , Riska Fii (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
This research aims to analyze the significance of the influence of work family conflict, work stress and workload on the performance of Niks Konveksi employees in Suarakarta. The type of data used in this research is quantitative data. The data source used is primary data. The population of this research is employees of Niks Konveksi in Surakarta. The sampling technique used a census technique with a sample size of 50 respondents. Data collection was carried out by distributing questionnaires to Niks Konveksi employees in Surakarta. The data analysis method in this research is multiple linear regression analysis using SPSS as a data processing tool. The research results show that work family conflict (X1) has no effect on employee performance, work stress (X2) has no effect on employee performance and workload (X3) has no effect on employee performance of Niks Convection in Surakarta. The R2 value of 49% means that the performance of Niks Konveksi employees in Surakarta can be explained by the variables work family conflict, work stress and workload, while the remaining 51% means that employee performance is explained by other variables, such as work motivation, work experience, work leadership, discipline. work, work ethics, work environment and so on which were not examined in this research.